Oral Administration of (S)-Allyl-l-Cysteine and Aged Garlic Extract to Rats: Determination of Metabolites and Their Pharmacokinetics - Park, Taehoon; Oh, Ju-Hee; Lee, Joo Hyun; Park, Sang Cheol; Jang, Young Pyo; Lee, Young-Joo (Planta Medica, 2017)
(S)-Allyl-l-cysteine is the major bioactive compound in garlic. (S)-Allyl-l-cysteine is metabolized to (S)-allyl-l-cysteine sulfoxide, N-acetyl-(S)-allyl-l-cysteine, and N-acetyl-(S)-allyl-l-cysteine sulfoxide after oral administration. An accurate LC-MS/MS method was developed and validated for the simultaneous quantification of (S)-allyl-l-cysteine and its metabolites in rat plasma, and the feasibility of using it in pharmacokinetic studies was tested. The analytes were quantified by multiple reaction monitoring using an atmospheric pressure ionization mass spectrometer. Because significant quantitative interference was observed between (S)-allyl-l-cysteine and N-acetyl-(S)-allyl-l-cysteine as a result of the decomposition of N-acetyl-(S)-allyl-l-cysteine at the detector source, chromatographic separation was required to discriminate (S)-allyl-l-cysteine and its metabolites on a reversed-phase C18 analytical column with a gradient mobile phase consisting of 0.1% formic acid and acetonitrile. The calibration curves of (S)-allyl-l-cysteine, (S)-allyl-l-cysteine sulfoxide, N-acetyl-(S)-allyl-l-cysteine, and N-acetyl-(S)-allyl-l-cysteine sulfoxide were linear over each concentration range, and the lower limits of quantification were 0.1 µg/mL [(S)-allyl-l-cysteine and N-acetyl-(S)-allyl-l-cysteine] and 0.25 µg/mL [(S)-allyl-l-cysteine sulfoxide and N-acetyl-(S)-allyl-l-cysteine sulfoxide]. Acceptable intraday and inter-day precisions and accuracies were obtained at three concentration levels. The method satisfied the regulatory requirements for matrix effects, recovery, and stability. The validated LC-MS/MS method was successfully used to determine the concentration of (S)-allyl-l-cysteine and its metabolites in rat plasma samples after the administration of (S)-allyl-l-cysteine or aged garlic extract.
Keywords: (S)-allyl-l-cysteine; Allium sativum; Alliaceae; LC-MS/MS; metabolism; garlic; pharmacokinetics